1982
DOI: 10.1016/s0022-5347(17)54131-2
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Study of Mineral Deposits in Idiopathic Calcinosis of the Scrotum

Abstract: An excised specimen from a 39-year-old man with idiopathic calcinosis of the scrotum was examined by electron microscopy. Mineral deposits were located in the dermis in which collagen fibers were numerous. These collagen fibers appeared mineralized to varying degrees. Mineral crystals frequently were present in the cytoplasm of fibroblasts near large deposits. The mineral portion was identified as a compound consisting of calcium and phosphorus, and the elementary mapping of calcium and phosphorus in the skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…Strong support for this view comes from Takayma et al. 8 who, in their careful electron microscopic study of a case, found no evidence of cyst remnants.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Strong support for this view comes from Takayma et al. 8 who, in their careful electron microscopic study of a case, found no evidence of cyst remnants.…”
Section: Discussionmentioning
confidence: 93%
“…They found no evidence of keratin in dermal tissue immediately adjacent to the calcium deposits and concluded that scrotal calcinosis was idiopathic. Strong support for this view comes from Takayma et al 8 who, in their careful electron microscopic study of a case, found no evidence of cyst remnants.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…were unable to find any cellular structures even in the smallest nodules and they supposed that idiopathic scrotal calcinosis is a degenerative phenomenon resulting from alterations in the chemical microenvironment leading to deposition of calcium and phosphorus. Takayama et al 10 . found mineral depositions located in the dermis and observed no calcifications or deposits in muscle cells by transmission electron microscopy.…”
mentioning
confidence: 97%